Kompetensi Guru Pendidikan Agama Islam (PAI) Menurut Undang-Undang No. 14 Tahun 2005 Relevansinya dengan QS al-Jumu’ah Ayat 2 - Nasiruddin Hidayah; Romlah Romlah (Intiqad: Jurnal Agama dan Pendidikan Islam, 2022)
This study aims to analyze the competence of Islamic Religious Education Teachers according to the provisions of Law No. 15 of 2005 its relevance to QS al-Jumu’ah paragraph 2, the research approach used is qualitative, the type of library research, the object of research is the law. Law number 15 of 2005 concerning teachers and lecturers, and the book of Tafsir ibn Kathir and Tafsir al-Azhar as well as other books or relevant journals. Data collection techniques with documentation using text content analysis techniques (content analysis) as a data analysis method by examining the relevance of the two provisions above. The results of the study show that the competence of teachers in Law No. 15 of 2005 has relevance to the contents of the QS letter al-Jumu’ah paragraph 2, namely yatlu 'alaihim relevant to professional and religious competence, yuzakkihim (Tazkiyah) relevant to personality and social competence, yu'allimum (Ta'lim) relevant to professional and pedagogical competence.